STRATEGY OF IMPLEMENTING ZERO WASTE BUSINESS MODEL IN COFFEE UMKM IN CENTRAL ACEH DISTRICT TOWARDS A SUSTAINABLE CIRCULAR ECONOMY - Dedy Darmansyah; Hartini; Riki Yulianda; Ina Yuyun (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study was conducted in Central Aceh Regency, known as one of the largest coffee producers in Indonesia. Coffee is an important economic sector for the local community, but challenges related to waste management and environmental sustainability are still significant. This study aims to analyze the zero waste business model strategy in coffee MSMEs using SWOT analysis and Importance Performance Analysis (IPA). The results of IPA indicate that technology adoption, infrastructure development, coffee derivative products, and government policies are important aspects that require more attention. However, the understanding of business actors, technology adoption, and consumer awareness are considered good and need to be maintained. Stakeholder involvement is considered sufficient, while supply chain efficiency meets expectations but does not require high priority. The SWOT analysis reveals that the strengths of coffee MSMEs include resources and access to technology that support the zero waste business model. However, the main weaknesses include limited understanding of business actors, inadequate infrastructure, and suboptimal development of coffee waste-based derivative products. Opportunities include supply chain efficiency, minimal similar competitors, and high consumer interest in innovation. On the other hand, the main threat comes from less supportive government policies.